Invariant natural killer T cell deficiency leads to the development of spontaneous liver inflammation dependent on γδT cells in mice - Nishio, Kumiko; Miyagi, Takuya; Tatsumi, Tomohide; Mukai, Kaori; Yokoyama, Yoshinobu; Yoshioka, Teppei; Sakamori, Ryotaro; Hikita, Hayato; Kodama, Takahiro; Shimizu, Satoshi; Shigekawa, Minoru; Nawa, Takatoshi; et al. (Journal of gastroenterology, 2015)
Background Immune tolerance is maintained in the liver, and perturbation of tolerance can lead to immune-mediated liver diseases such as autoimmune hepatitis (AIH). Invariant natural killer T (iNKT) cells and γδT cells have been shown to maintain immune homeostasis as regulatory cells and to play pathogenic roles in immune-mediated diseases as effector cells. We hypothesized that iNKT cells and γδT cells are involved in the maintenance of hepatic immune tolerance and immune-mediated liver disease. Methods We measured liver inflammation and the cytokine profiles of liver mononuclear cells in BALB/c wild-type (WT) mice and BALB/c Jα18-deficient (KO) mice lacking iNKT cells. We also examined the role of γδT cells in AIH using liver tissue from AIH patients and control subjects. Results Spontaneous liver inflammation, hepatocyte damage, and anti-nuclear-antibody production occurred in Jα18 KO mice but not in WT mice. Furthermore, liver mononuclear cells from Jα18 KO mice, but not those from WT mice, produced interleukin-17 (IL-17). γδT cells were the primary producers of the cytokine, and they were more abundant in the livers of Jα18 KO mice than in those of WT mice. In Jα18 KO mice, the administration of anti-γδT-cell-receptor antibody abolished liver inflammation, hepatocyte damage, and IL-17 production. γδT cells accumulated in the livers of AIH patients but not in those of the control subjects. Conclusions Our results suggest a protective role for iNKT cells, a pathologic role for γδT cells, and an association between these cells in the pathogenesis of AIH.